ASSESSING THE EFFECTS OF THE 2019 FLOOD IN YOBE STATE COMMUNITIES AND POSSIBLE MITIGATION APPROACH - Gana, A. H.; Salisu, K. (FUDMA JOURNAL OF SCIENCES, 2020)
Flood is one of the natural disasters that cause serious damage to property, environment and human livelihood. Intergovernmental Panel on Climate Change (IPCC) reports over the years have indicated that climate related disasters will more than double between 2000 to 2050 in comparison to their occurrence in the 20th century. It is evident that many communities around the world are becoming vulnerable to flood. Vulnerability is shaped by internal factors which (e.g poverty, age, weakness) these increase the degree of human exposure, and the external factors include (e.g susceptibility to climate change and socio-economic factors). It also depends on the sensitivity and adaptive capacity of a system to natural disasters. This study assessed the impacts of the 2019 flood in Yobe State, where data were obtained through Yobe State Emergency Management Agency (YOSEMA). YOSEMA is among the governmental organisations in the state that provides support and relief to flood victims and affected households. Secondary data was collected from YOSEMA (2019 flood report) to assess affected households and communities in the state. The 2019 flood events have affected over 5,000 households and had caused 4 deaths in the state. In this study, Holistic Flood Mitigation Approach was proposed to improve flood mitigation measures. This approach advocates for shifts from reactive approach (relief) to proactive approach (reduce risk). This can be conducted using the vulnerability indicators for the holistic approach. Further studies will be conducted to assess the level of household vulnerability in order to understand the recovery pace of communities